4D BIM for Environmental Planning and Management. (2017) - Jupp, Julie
Abstract: For more than a decade research has shown that 4D Building Information Modelling (BIM) can improve construction planning, scheduling and production control as well as the onsite management of safety, workspaces and waste. The increasing use of 4D BIM in construction highlights opportunities for utilising these capabilities in new digital management systems replete with role reorganization, new practices and workflows, and not solely as a tool for constructability analysis and onsite monitoring of construction progress. Continued focus on construction-based environmental impacts provides an impetus to leverage 4D BIM to improve communication and information flow throughout environmental planning and management tasks. This paper explores how environmental planning and management can be supported by 4D capabilities. 4D modelling and analysis technologies combined with structured workflows are presented as the basis for developing a tailored framework for environmental planning and management. Five functional prerequisites necessary to the collaborative development and onsite monitoring of environmental management systems are identified before laying out the directions for future research.